Development of Copper-based Metal Organic Framework HKUST-1 /Cellulose Acetate Mixed-Matrix Membane for CO2/CH4 Removal - Ayub, Nur Athirah (Universiti Teknologi PETRONAS, 2016)
Natural gas that has high content of CO2 is a crucial issue, since it will lower the value of the resource. Membrane separation has displayed better potential to remove CO2 from natural gas compared to other gas separation technologies. Therefore, development of a high selective membrane material for the enhancement of CO2/CH4 separation performance is the main focus of this project. A series of mixed-matrix membranes (MMMs) by incorporating copper-based metal-organic framework, HKUST-1 into cellulose acetate polymer matrix were fabricated in this work. Synthesized HKUST-1 was characterized using SEM and FTIR. The fabricated membranes were characterized as well using SEM, EDX, and ATR-FTIR The performance of the resultant membranes were also tested for CO2 and CH4 gases permeation. The SEM images of HKUST-1 illustrates that the crystalline structure of the particles were octahedral in shape with an average diameter of 16-36 µm.